Institutional Constraints for the Success of Agricultural Biotechnology in Developing Countries: The Case of Bt-Cotton in Shandong Province, China - Hermann Waibel; Diemuth E. Pemsl; Andrew P. Gutierrez (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
The use of genetically engineered crop varieties has recently become one option to prevent pest damage in agriculture. The promoters of biotechnology stress the great potential for yield increase and pesticide reduction while the critics point out the potential risks for biodiversity and human health as well as institutional problems for implementation especially in developing countries. The objective of this paper is an in-depth economic analysis of Btcotton production in North East China under small-scale conditions and several years after technology introduction. Data were collected in 2002 (March - October) in Linqing County, a major cotton growing area of Shandong Province, China. Data collection comprised a seasonlong monitoring of Bt-cotton production with 150 farmers from five villages, and three complementary household interviews. In addition, plot-level biological testing was carried out to determine the actual Bt toxin concentration in the varieties that were used by the farmers. All farmers in the case study were growing insect resistant Bt-cotton varieties in 2002. Nevertheless, they sprayed high amounts of chemical pesticides that were almost entirely insecticides. A proportion of 40% of the pesticides applied belonged to the categories extremely or highly hazardous (WHO classes Ia and Ib). The paper reviews methodological issues inherent to impact assessment of crop biotechnology and identifies market and institutional failure as possible reasons for continued high pesticide use. The production function methodology with damage control function was applied and it was found that for both damage control inputs, i.e. Bt and insecticides the coefficients were not significantly different from zero. In contrast to studies that treat Bt varieties as dummy variable in economic models, in this research it was possible to specify Bt toxin concentration in cotton leaf samples as a continuous variable. The results of this study support the notion that introducing Biotechnology in developing countries without enabling institutions that assure proper use of the technology can considerably limit its benefits. Hence it is important to include institutional criteria in the evaluation of agricultural biotechnology especially in developing countries.
Keywords: 330